2015
DOI: 10.1186/s12890-015-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the global lung function initiative 2012 reference values for spirometry in a Swedish population sample

Abstract: BackgroundThe Global Lung Function Initiative 2012 (GLI) reference values are currently endorsed by several respiratory societies but evaluations of applicability for adults resident in European countries are lacking. The aim of this study was to evaluate if the GLI reference values are appropriate for an adult Caucasian Swedish population.MethodsDuring 2008–2013, clinical examinations including spirometry were performed on general population samples in northern Sweden, in which 501 healthy Caucasian non-smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
119
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(141 citation statements)
references
References 27 publications
21
119
1
Order By: Relevance
“…Table 4 presents the main characteristics and results of some studies reporting Z-scores data [1420] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 presents the main characteristics and results of some studies reporting Z-scores data [1420] .…”
Section: Discussionmentioning
confidence: 99%
“…The age scattering and other anthropometric, ethnic, socioeconomic and environmental factors should be equivalent since such factors can mark lung function [14] . Furthermore, the methodology for performing spirometric tests ( eg ; protocol and equipment) must be stringent [4, 25] .…”
Section: Introductionmentioning
confidence: 99%
“…The Global Lung Function Initiative (GLI) 2012 therefore developed a new set of multiethnic predicted normal equations [4, 5] using the pooled resources of 26 countries and data from more than 74000 subjects. They have been evaluated and shown to be well matched to some adult populations (in Australasia [6] and Europe [7, 8]) but not others, such as Finland [9] and Sweden [10], where local population-specific reference values may be more relevant. Therefore, care needs to be taken when recommending whether GLI equations should be implemented in any particular population or laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we found z-score means closer to zero and that sex differences disappeared when GLI equations were used (table 1). BACKMAN et al [3] showed that GLI equations better described a healthy Swedish population than the ECSC equations, but the average z-scores of each parameter were further from zero than ours when applying the GLI reference values. For example, the mean z-score was 0.41±0.92 versus 0.24±0.98 for FVC and 0.25±0.86 versus 0.03±1.00 for FEV1, respectively, among women in the Swedish study versus women in our northern French population.…”
mentioning
confidence: 99%
“…BACKMANet al [3] have recently shown that the GLI reference values were better suited than the ECSC reference values to the Swedish population but less relevant than local population-specific reference values. In particular, forced volume capacity (FVC) and forced expiratory volume in 1 s (FEV1), expressed as percentages of predicted values, tended to be overestimated among women to a greater extent by the ECSC reference values than the GLI values.…”
mentioning
confidence: 99%